SYNTHESIS AND CHARACTERIZATION OF 5-SALICYLIDENEIMINO-1,10-PHENANTHROLINE AND ITS Ni(II), Co(II) COMPLEXES - Elmali, Fikriye Tuncel; Demirhan, Nebahat; Duman, Hakan; Avciata, Ulvi (WALTER DE GRUYTER GMBH, 2009)
As a multidonor ligand with phenanthroline and salicylaldimine functionalities on the same molecule, 5-salicylideneimino-1,10-phenanthroline (LH) has been synthesized by the reaction of 5-amino-1,10-phenanthroline with salicylaldehyde and its metal complexes with Ni(II) and Co(II) have been prepared. The structures of the ligand and its complexes have been characterized by elemental analyses, FTIR, H-1 NMR, C-13 NMR, LC-MS spectra, magnetic measurements and TGA-DSC-DTG techniques. The ligand, Ni(II) and Co(II) complexes have been studied potentiometrically. The metal to ligand ratio of the Ni(II) and Co(II) complexes was found to be 1:2. Protonation constants of LH2+ which have been determined by potentiometric titration are log K-1 = 10.99, log K-2 = 8.00.
Keywords: Synthesis; Schiff base; Ni(II) and Co(II) complexes; protonation constants; TRANSITION; NICKEL(II); COPPER(II); Chemistry